Little Whistle - Rylant, Cynthia; Bowers, Tim (Orlando : Harcourt, 2003)
At night after the shades are drawn, a small guinea pig shares adventures with the toys in Toytown, the toy store where he lives.
"Voyager books."
3.5
K-3
K-3
School Library Journal
Publisher's Weekly
Keywords: Guinea pigs -- Fiction; Toys -- Fiction; Night -- Fiction; Guinea pigs -- Fiction; Toys -- Fiction; Night -- Fiction